Hubungan Status Gizi dan Persen Lemak Tubuh Remaja Putri di SMPN 13 Jember - Adelina, Anugerah Eka; Jamhariyah, Jamhariyah; Gumiarti, Gumiarti (Jember Maternal and Child Health Journal; Vol 1 No 2 (2024): Jember Maternal and Child Health Journal, 2024)
Background : Menarche is when a girl menstruates for the first time and is influenced by various factors, including nutritional status and body fat percentage. The average age of menarche of adolescent girls in Indonesia is 12.96 years, while in East Java at the age of 12.56 years. The results of a preliminary study of 10 female students, 30% with obese nutritional status experienced early menarche and 70% with good nutritional status 30% experienced late menarche and 40% normal menarche. This study aims to analyse the relationship between nutritional status and percent body fat with the age of menarche of adolescent girls. Methods : Analytical observational research design with a cross-sectional approach in 60 adolescent girls with saturated sampling technique. Analysis with Spearman Rank Test. Results : 51.7% good nutritional status, 18.3% undernutrition status, 16.7% obese nutritional status, 13.3% overnutrition status. 56% healthy, 20% underfat, 11% overfat and 11% obese. 56.7% normal menarche, 23.3% late menarche and 20% early menarche. There was a very strong relationship between nutritional status and menarche age of adolescent girls (p-value 0.000, rs=0.924). There is a very strong relationship between percent body fat and menarche age of adolescent girls (p-value 0.000, rs=0.997). Conclusion : Good nutritional status and ideal body fat percent are likely to experience menarche at a normal age. Adolescent girls can implement balanced nutrition by paying attention to daily nutritional needs and monitoring nutritional status regularly